Effect of Er:YAG Laser on Shear Bond Strength of Composite to Enamel and Dentin of Primary Teeth - Zahra Bahrololoomi; Mona Kabudan; Leila Gholami (Frontiers in Dentistry, 2015)
Objectives: Bond strength of composite resin to enamel and dentin of primary teeth is lower than that to permanent teeth; therefore, it may compromise the ad- hesive bonding. New methods, such as laser application have been recently intro- duced for tooth preparation. The purpose of this study was to evaluate the effect of tooth preparation with bur and Er:YAG laser on shear bond strength of com- posite to enamel and dentin of primary teeth.